Assessing the Ecological Variation in the Police Response to Hate Crime: Evidence From New York City - Holder, Eaven (Criminal justice review, 2025)
As scholarly attention toward the etiology of hate crime offending and victimization continues to grow, there remain some empirical gaps regarding criminal justice interventions to such crimes. The lion's share of research has been focused on how agencies report bias crimes to official sources like the FBI's Uniform Crime Reporting program, but less work has been spent studying other aspects of police response like investigation or arrest. However, even less is known in whether an officer's ecological context is influential in this process despite space being vital to policing in general. To address this, we combined incident- and precinct-level data from the New York Police Department with neighborhood census information to understand if community dynamics were associated with the likelihood that a reported hate crime would be cleared through arrest. Using mixed effects models, our findings indicate some degree of clustering in hate crime clearances but that situational factors emerged with greater salience in the prediction of arrest. Supportive more so of the schema and focal concerns perspective of criminal justice processing, we offer pathways for future research and theoretical considerations.